Electoral system effects re-examined using the largest vote share variable. Issue 1 (2nd January 2018) - Li, Yuhui
ABSTRACT: In the search for a less controversial pattern between electoral systems and party systems, especially the institutional conditions for multipartism, this article develops and analyses a complete post-war dataset on largest parties' vote shares. In contrast to the vague wording in the Duvergerian literature, it defends a strong proposition that majority parties are almost always a result of disproportionality. With some rare exceptions, they are either manufactured (without a majority of popular votes) or, less frequently, held together by heterogeneous groups (indicated either by a large number of swing voters or an exceptionally restrictive system) through strategic voting. I explain the phenomenon using a theory on politicians' incentive for office turnover and voters' demand for party accountability, and also theorize why South Africa and Namibia are the only two outliers to the pattern.